The biodiversity and biotic integration in the oak-wood of middle Russian partially wooded steppe districts - V. I. Reutskaya; U. Ph. Arefiev (Юг России: экология, развитие, 2015)
In this article there are givin the problems of biotic integration in the oak-wood of partially wooded steppe destrikts. There was studying the vitality dependens of oaks from their composition diversity.